Anticancer activity studies of some cyclic benzimidazole derivatives - El-Shekeil, Ali; Obeid, Abeer Omer; Al-Aghbari, Sama (European Journal of Chemistry, 2012)
New benzimidazole derivatives, namely, (N-(4-methoxyphenyl)methylene]-1H-benzimidazol-2-amine (2a), (N-(3,4-dimethoxyphenyl)methylene]-1H-benzimidazol-2-amine (2b), and (N-(3,4,5-trimethoxyphenyl)methylene]-1H-benzimidazol-2-amine (2c) were synthesized by reaction of a Schiff base with malononitrile in absolute ethanol. Structures of compounds have been confirmed by IR, 1H NMR and elemental analysis. Compounds 2a-c were screened for their in vitro anticancer potential using HeLa and PC3 cells. All compounds showed limited cytotoxicity except compound 2a that showed a moderate cytotoxic effect towards HeLa cells.